PSYCHOLOGICAL ASPECTS OF ACTIVATION OF CREATIVE MATHEMATICAL THOUGHT - Мойсеєнко, Л. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The psychological aspects of activation and optimization of creative thought are analysed. Described terms of conducting of training directed on a thought process. The psychological bases of introduction of the creative training for activation of creative mathematical thought are examined. Attention on the necessity of activation of constituents of decision of creative mathematical tasks is accented: process of understanding, process of prognostication, process of approbation. Possibility of positive influence on quality of creative mathematical thought by the treningovoi system CAROUS and approbation of tasks by the series of the special questions are mentioned.